Redefinisi “Perbatasan dan Keamanan” di Asia Tenggara (Sebuah Paradigma untuk Ketahanan Nasional) - Kamaruzzaman Bustamam-Ahmad (Jurnal Ilmu Sosial dan Ilmu Politik, 2011)
This article intends to examine the dynamics of "border and security" in Southeast Asia through the social history approach. ASEAN members have used the concept of ASEAN Community by 2015 as a new way of building community identity of Southeast Asia. This study described how changes in paradigm to the concept of "borders and security" by examining the meaning of nation, homeland, and the influence of the post-colonial concept of nation states. Here is explained the concept of security, faith, salvation as a fundamental concept in the "border and security" which has been influenced by religious values. Authors concluded that the concept of ASEAN Community is one way of raising a new paradigm among the members of the organization-although not entirely successful in practice-towards an identity and vision among the people of Southeast Asia.